Dicyanopyrazine capped with tetraphenylethylene: polymorphs with high contrast luminescence as organic volatile sensors. (12th September 2016) - Ge, Chao; Liu, Yang; Ye, Xin; Zheng, Xiaoxin; Han, Quanxiang; Liu, Jie; Tao, Xutang
Abstract : TPE-caped dicyanopyrazines with morphology dependent and reversible luminescence can be utilized as VOC sensors. Abstract : Recently the polymorphism and phase-transition between polymorphs have attracted special attention in organic luminescent materials. In this report, we employed propeller-like tetraphenylethylenes to functionalize large conjugated and electron-withdrawing dicyanopyrazine units, constructing novel organic luminescent polymorphs with high contrast fluorescence. Through an in-depth study of the luminescence-related properties, the more planar structured2DQCN was found to generate close intermolecular packing and demonstrated essentially different solid state luminescence behaviour compared with that of1DQCN . It shows crystallization-induced red-shift fluorescence, in contrast to the crystallization-induced blue-shift of1DQCN and many other AIE (aggregation-induced emission) materials. The morphology transformation of2DQCN can be realized via solvent fuming and thermal annealing, where the transformation among its three forms was manifested by DSC measurements. Utilizing the high contrast luminescence of2DQCN polymorphs, we demonstrated their real applications as selective visual sensors for detecting volatile organic compounds. The results, revealing insights into the structure–property relationship of luminescent polymorphs, should provide useful directions for the understanding, design and utilization of luminescent colour-switching materials.